Ischemic insults induce necroptotic cell death in hippocampal neurons through the up-regulation of endogenous RIP3 - Vieira, M.
Global cerebral ischemia induces selective acute neuronal injury of the CA1 region of the hippocampus. The type of cell death that ensues may include different programmed cell death mechanisms namely apoptosis and necroptosis, a recently described type of programmed necrosis. We investigated whether necroptosis contributes to hippocampal neuronal death following oxygen-glucose deprivation (OGD), an in vitro model of global ischemia. We observed that OGD induced a death receptor (DR)-dependent component of necroptotic cell death in primary cultures of hippocampal neurons. Additionally, we found that this ischemic challenge upregulated the receptor-interacting protein kinase 3 (RIP3) mRNA and protein levels, with a concomitant increase of the RIP1 protein. Together, these two related proteins form the necrosome, the complex responsible for induction of necroptotic cell death. Interestingly, we found that caspase-8 mRNA, a known negative regulator of necroptosis, was transiently decreased following OGD. Importantly, we observed that the OGD-induced increase in the RIP3 protein was paralleled in an in vivo model of transient global cerebral ischemia, specifically in the CA1 area of the hippocampus. Moreover, we show that the induction of endogenous RIP3 protein levels influenced neuronal toxicity since we found that RIP3 knock-down (KD) abrogated the component of OGD-induced necrotic neuronal death while RIP3 overexpression exacerbated neuronal death following OGD. Overexpression of RIP1 also had deleterious effects following the OGD challenge. Taken together, our results highlight that cerebral ischemia activates transcriptional changes that lead to an increase in the endogenous RIP3 protein level which might contribute to the formation of the necrosome complex and to the subsequent component of necroptotic neuronal death that follows ischemic injury.